Filter to Retrieve Studies Related to Indigenous Peoples of the Northwest Territories in the OVID MEDLINE Database ... - Tjosvold, Lisa; Campbell, Sandy; Dorgan, Marlene (University of Alberta Library, 2013)
This is one of a suite of filters designed to retrieve studies related to Canadian Indigenous Peoples from the OVID MEDLINE database. This filter is specific to the Northwest Territories. ...